Sleep duration and risk of end-stage renal disease: the Singapore Chinese Health Study - Geng, Ting-Ting (Sleep Med, 2018)
OBJECTIVES: Although epidemiological evidence suggests that short sleep duration may affect renal function, the influence of long sleep and risk of end-stage renal disease (ESRD) is unclear. We examined the association between sleep duration and risk of ESRD. METHODS: We investigated sleep duration and ESRD risk in the Singapore Chinese Health Study, a prospective population-based cohort of 63,257 Chinese in Singapore, who were aged 45–74 years at recruitment (1993–1998). Information on daily sleep duration (including naps), diet, medical history and other lifestyle factors was collected at recruitment from in-person interviews. ESRD cases were identified via linkage with the nationwide Singapore Renal Registry through year 2014. We used the Cox proportional hazards regression method to estimate hazard ratio (HR) and 95% confidence interval (CI) of ESRD in relation to sleep duration. RESULTS: After an average 16.8 years of follow-up, 1,143 (1.81%) ESRD cases were documented. Sleep duration had a U-shaped association with risk of ESRD (P for quadratic trend < 0.001). Compared with participants with 7 hours/day of sleep, the multivariable adjusted HR (95% CI) of ESRD was 1.43 (1.18–1.74) for short sleep (≤ 5 hours/day) and 1.28 (1.03–1.60) for long sleep duration (≥ 9 hours/day). The increased risk was stronger in participants with more than 10 years of follow-up compared to those with shorter follow-up time, especially for long sleep (P for interaction = 0.003). CONCLUSIONS: Our findings demonstrated that both short and long sleep durations were associated with a higher risk of ESRD in this Asian population.